PERANCANGAN MODEL PENGUKURAN KINERJA GREEN LOGISTICS DENGAN METODE GREEN SUPPLY CHAIN OPERATIONS REFERENCE - Hanifah, Cahyarani Adi; Surachman, Surachman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
PT X is a logistics company that has been operating in Indonesia since 2015. This company, based on the observations, has already been aware of green logistics business process as they partner with Kamibox for solid waste processing and with Blitz for the operation of green-fuel vehicles. However, the company has not applied any performance measurement in their green logistics business. The measurement was designed using qualitative method, from which indicators based on the Green Supply Chain Operations Reference (GreenSCOR) were acquired. The components of GreenSCOR used in this research are Source, Deliver, Return, dan Waste Management. This research results in ten Key Performance Indicators. Then, based on the preset performance measurement, the score of the Green Logistics performance is 89, categorized as good. Further, three indicators were found to have values that are lower than the average; they are K1 (yellow category) and K8 and K10 (red category). The output of this research is a design of Green Logistics performance measurement recommended to the company for application.